A new species of the whip spider genus \(Weygoldtia\) (Arachnida: Amblypygi: Charinidae) from Con Dao National Park, Vietnam - Anh, Nguyen Thi Thu; Hong Luong, Phung Thi (Academia Journal of Biology, 2022)
A new species of the monotypic genus Weygoldtia Miranda, Giupponi, Prendini & Scharff, 2018 was described from Con Son island, southern Vietnam, namely Weygoldtia condao sp. nov. The new species is clearly distinguished from its congener Weygoldtia davidovi (Fage, 1946) by having more articles in the tibia and tarsus of leg I. A fragment of the cytochrome c oxidase subunit I (COI) gene is also provided for the new species. The K2P genetic distance of the COI between the new species and W. davidovi is 20%, and phylogenetic analysis also supported the new species.